Do Food Price Subsidies Increase Nutritional Intake of Indonesian Households? - Eka Rastiyanto Amrullah; Pepi Nur Susilawati; Ismatul Hidayah; Aris Rusyiana; Akira Ishida (Universitas Muhammadiyah Yogyakarta, 2023)
Indonesia's economy has developed rapidly, but it has not solved undernourishment issues among low-income people. Therefore, similar to other developing countries, Indonesia has instituted a food price subsidy program known as Rice for the Poor (RASKIN) to help low-income families meet their needs and alleviate some of their financial burdens. This study examined how RASKIN affected the intake of calories and three macronutrients of Indonesian households using the representative National Socioeconomic Survey (SUSENAS) data. In comparison to intake without the subsidy, the estimation results based on the endogenous switching regression model suggested that receiving the subsidy raised the household calorie intake by 368.4 Kcal/day for recipients and 454.6 Kcal/day for nonrecipients. Likewise, households receiving the subsidy raised their macronutrient intake, encompassing protein, carbohydrate, and fat, compared to those not receiving it. Therefore, RASKIN contributed to raising the intake of calories and three macronutrients. However, a certain portion of non-poor households were found to receive RASKIN owing to mistargeting, suggesting that the government should rectify targeting errors to enhance the effectiveness of the subsidy and attain the key purpose of improving the well-being of people with low incomes.